1989
DOI: 10.1002/jat.2550090108
|View full text |Cite
|
Sign up to set email alerts
|

Nasal tumours in rats after severe injury to the nasal mucosa and prolonged exposure to 10 ppm formaldehyde

Abstract: To study the significance of damage to the nasal mucosa for the induction of nasal tumours by formaldehyde in rats, a long-term inhalation study was conducted in which male rats with severely damaged or undamaged nose were exposed 6 h/day for 5 days/week to 0, 0.1, 1.0 or 10 ppm formaldehyde vapour for 28 months, or for 3 months followed by a 25-month observation period. The damage to the nasal mucosa was induced by bilateral intranasal electrocoagulation. The total number of rats used was 720, 480 with damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 8 publications
1
30
0
1
Order By: Relevance
“…These formaldehyde associated metaplastic changes are morphologically distinct from the more progressive B[a]P-associated phenotypic alterations (I 58, 165). The occurrence of epithelial cell injury enhances carcinogenesis in rats chronically exposed to formaldehyde (206). In hamsters exposed to a chronic (lifetime) dose of formaldehyde, Dalbcy (28) found that diethylnitrosamine (DEN) treated animals developed more tumors per trachea than animals exposed to DEN alone.…”
Section: Cohimunicationmentioning
confidence: 99%
“…These formaldehyde associated metaplastic changes are morphologically distinct from the more progressive B[a]P-associated phenotypic alterations (I 58, 165). The occurrence of epithelial cell injury enhances carcinogenesis in rats chronically exposed to formaldehyde (206). In hamsters exposed to a chronic (lifetime) dose of formaldehyde, Dalbcy (28) found that diethylnitrosamine (DEN) treated animals developed more tumors per trachea than animals exposed to DEN alone.…”
Section: Cohimunicationmentioning
confidence: 99%
“…Squamous cell carcinomas of the respiratory epithelium were also found in Cpb:WU (Wistar random) rats with their respiratory mucosa severely damaged by electrocoagulation and exposure to 10 ppm formaldehyde for 28 months (11). The only squamous cell carcinoma found to have metastasized to the lungs was present in a rat exposed to acetaldehyde (Plate 4).…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, the observed histological alterations in the pulmonary epithelium ranged from acute interstitial inflammation (pnuemonitis), pulmonary fibrosis, acute purulent bronchitis, acute lung injury and chronic lung injury; similar to that reported by Kamta et al (1996). Similarly, the studies of Woutersen et al (1989) revealed nasal lesions of respiratory epithelium and yellowing of the fur. The lesions consisted rhinitis squamous metaplasia and basal cell/psuedoepithelial hyperplasia which is in agreement with the observations revealed in my studies which include yellowing of the fur and also nasal lesions in the respiratory epithelium.…”
Section: Discussionmentioning
confidence: 85%